Sexual Function and Pessary Management Among Women Using a Pessary for Pelvic Floor Disorders. (1st December 2015) - Meriwether, Kate V.; Komesu, Yuko M.; Craig, Ellen; Qualls, Clifford; Davis, Herbert; Rogers, Rebecca G.
ABSTRACT: Introduction: Pessaries are commonly used to treat pelvic floor disorders, but little is known about the sexual function of pessary users. Aim: We aimed to describe sexual function among pessary users and pessary management with regard to sexual activity. Methods: This is a secondary analysis of a randomized trial of new pessary users, where study patients completed validated questionnaires on sexual function and body image at pessary fitting and 3 months later. Main Outcome Measures: Women completed the Pelvic Organ Prolapse—Urinary Incontinence Sexual Function Questionnaire, International Urogynecological Association Revised (PISQ-IR), a validated measure that evaluates the impact of pelvic floor disorders on sexual function, a modified female body image scale (mBIS), and questions regarding pessary management surrounding sexual activity. Results: Of 127 women, 54% (68/127) were sexually active at baseline and 42% (64/114) were sexually active at 3 months. Sexual function scores were not different between baseline and 3 months on all domains except for a drop of 0.15 points ( P = 0.04) for sexually active women, and a drop of 0.34 points for non-sexually active women ( P = 0.02) in the score related to the sexual partner. Total mBIS score did not change ( P = 0.07), but scores improved by 0.2 points ( P = 0.03) in the question related to self-consciousness. Pessary satisfaction was associated with improved sexual function scores in multiple domains and improved mBIS scores. The majority (45/64, 70%) of sexually active women removed their pessary for sex, with over half stating their partner preferred removal for sex (24/45, 53%). Conclusion: Many women remove their pessary during sex for partner considerations, and increased partner concerns are the only change seen in sexual function in the first 3 months of pessary use. Pessary use may improve self-consciousness and pessary satisfaction is associated with improvements in sexual function and body image.